Max Weber’s methodological individualism - Schwinn, Thomas (The Palgrave Handbook of Methodological Individualism, 2023)
In the methodological debates, most diverse theoretical currents repeatedly refer to Max Weber. However, a satisfactory reconstruction of Weber's methodology is still lacking. The article displays the conceptual tools with which he tries to get a grasp on the micro-macro link. With the concept of chance, the ideal type and the types of social action, a differentiated action-order connection is possible. This model allows insight into the reproduction mode of social orders and gives the possibility of grasping the empirically interesting intermediate stages and transitional processes of orders. Avoiding reductionism and a differentiated conception of action and order make Weber an interesting discussion partner in the current discussion.